DNA damage response at telomeres boosts the transcription of SARS‐CoV‐2 receptor ACE2 during aging. (2nd December 2021) - Sepe, Sara; Rossiello, Francesca; Cancila, Valeria; Iannelli, Fabio; Matti, Valentina; Cicio, Giada; Cabrini, Matteo; Marinelli, Eugenia; Alabi, Busola R; di Lillo, Alessia; Di Napoli, Arianna; Shay, Jerry W; et al.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) causes the coronavirus disease 2019 (COVID‐19), known to be more common in the elderly, who also show more severe symptoms and are at higher risk of hospitalization and death. Here, we show that the expression of the angiotensin converting enzyme 2 (ACE2), the SARS‐CoV‐2 cell receptor, increases during aging in mouse and human lungs. ACE2 expression increases upon telomere shortening or dysfunction in both cultured mammalian cells and in vivo in mice. This increase is controlled at the transcriptional level, and Ace2 promoter activity is DNA damage response (DDR)‐dependent. Both pharmacological global DDR inhibition of ATM kinase activity and selective telomeric DDR inhibition by the use of antisense oligonucleotides prevent Ace2 upregulation following telomere damage in cultured cells and in mice. We propose that during aging telomere dysfunction due to telomeric shortening or damage triggers DDR activation and this causes the upregulation of ACE2, the SARS‐CoV‐2 cell receptor, thus contributing to make the elderly more susceptible to the infection. Synopsis: During aging, telomere dysfunction accumulates and activates a DNA damage response, leading to increase of ACE2, the human SARS‐CoV‐2 receptor. This mechanism may explain the higher susceptibility of elderly to COVID‐19. ACE2 expression increases with aging in human and mouse lungs. DNA damage response activation, including when triggered by telomere dysfunction, increases ACE2 expression levels. Telomere‐specific antisense oligonucleotide (ASO)‐mediated telomeric DNA damage response inhibition prevents the increase of ACE2 levels in mice. Abstract : During aging, telomere dysfunction accumulates and activates a DNA damage response, leading to increase of ACE2, the human SARS‐CoV‐2 receptor. This mechanism may explain the higher susceptibility of elderly to COVID‐19.